Corpo e espírito: representações da homossexualidade no espiritismo - Guimarães, Fernando Augusto de Souza (2018)
The aim of this research was analyzed the way which spiritist theory, by the belief in reincarnation and immortality of the spirit, explain a sexual diversity. The analysis took by goal the specificity which the homosexuality is understood. Therefore, it was compared the representations on the homosexuality in two dimensions of the spiritism: institutional level and the religious base. The consideration on institutional dimension it was from some literary works concerned with this topic and, mainly, at the discourse of Andrei Moreira, ex-president of the Associação Médico-Espírita de Minas Gerais (AME-MG), in his book: A homossexualidade sob a ótica do espírito imortal. Subsequently, the research became turned to the way which members of two spiritist centers in the state of São Paulo, Centro Espírita Amor e Caridade e Centro Espírita Casa do Caminho, precisely in the cities of Bauru and São Carlos, deal with the question about sexuality. Starting from the hypothesis of great majority of brasilians, incluing spiritists, aren’t receptive to individuals LGBT (lesbians, gays, bisexuals and transgenders), this research has as its core the approach the contrast between the acceptance discourse in the institutional level which the limited degree of real acceptance of this sexualities in the context of the interior state of São Paulo. Based on the foundations of Michel Foucault and the proposals of queer studies, were taken as a basis of spiritist discourse about sexuality, further then Andrei Moreira’s book, the following ones: Homossexualidade, reencarnação e vida mental by Walter Barcelos; Vida e Sexo by Francisco Cândido Xavier saying by Emanuel spirit and Além do azul e do rosa – recortes terapêuticos sobre a homossexualidade à luz da doutrina espírita, wrote by Gibson Bastos and Sexo e Consciência, wrote by Divaldo Franco, Encontro com a paz e a saúde e Constelação familiar, by Divaldo Franco saying by Joanna Ângelis spirit, and last Sexo e sexualidade de Regis de Moraes. After that, semi-structured interviews were conduct with some national and international spiritist leaders. This data were cross-referenced with the results through semi-structured interviews with representatives of both centers with data collected in field work. Finally, in terms of conclusion, this work introduce the way which the believes in reincarnation and immortality of spirit enable the comprehension of homosexuality as natural and normal, in addition it was possible contribute which a greater understanding of the dynamics of functioning of the spiritist movement